2000
DOI: 10.1103/physrevb.61.7203
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of anomalous optical transitions inAlxGa1xNalloys

Abstract: We present a comprehensive study of the optical characteristics of Al x Ga 1Ϫx N epilayers (0рxр0.6) by means of photoluminescence ͑PL͒, PL excitation, and time-resolved PL spectroscopy. For Al x Ga 1Ϫx N with large Al content, we observed an anomalous PL temperature dependence: ͑i͒ an ''S-shaped'' PL peak energy shift ͑decrease-increase-decrease͒ and ͑ii͒ an ''inverted S-shaped'' spectral width broadening ͑increasedecrease-increase͒ with increasing temperature. We observed that the thermal decrease in integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
82
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 17 publications
(16 reference statements)
9
82
2
Order By: Relevance
“…This trend is expected because the increase in E a should reflect an increase in trapping sites near the grain boundaries as AlN composition increases. 17,25 This is in line with the AFM results that show an increase in the density of grain boundaries with increasing AlN concentration. Although the thermal response of carrier lifetime generally gives a more accurate estimation of E a when the radiative lifetimes of the carriers are temperature- dependent, 26 the increase in E a derived from integrated PL intensity with AlN composition has been also reported in extant literature and was linked to an increase in trapped states.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…This trend is expected because the increase in E a should reflect an increase in trapping sites near the grain boundaries as AlN composition increases. 17,25 This is in line with the AFM results that show an increase in the density of grain boundaries with increasing AlN concentration. Although the thermal response of carrier lifetime generally gives a more accurate estimation of E a when the radiative lifetimes of the carriers are temperature- dependent, 26 the increase in E a derived from integrated PL intensity with AlN composition has been also reported in extant literature and was linked to an increase in trapped states.…”
supporting
confidence: 78%
“…16 On the other hand, the departure from Varshni's bandgap shrinkage model at temperatures higher than 150 K is most likely a result of thermally induced carrier population of the bandtail states. 17 In addition, sample D with lowest AlN composition shows an initial redshift followed by a final blueshift. This behavior has been reported in PbS quantum dot (QD) systems and in self-organised InGaN QDs, where it was attributed to thermally induced carrier trapping in shallow states.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 However, these results point out that an increase of potential fluctuations can occur with well thickness as well. Previously, several reports suggested that the localized states may arise from In compositional fluctuation or QD formation, phase separation, monolayer thickness fluctuation, and surface segregation.…”
mentioning
confidence: 47%
“…It is known in AlGaN alloys grown by MOCVD that there are random fluctuations in the potential due to alloy fluctuations [16][17][18] and this gives rise to carrier localization. Thus, taking into account results of the TRPL measurements and the calculated band structure, we suggest that the AlGaN related emission likely occurred between electrons strongly confined in the triangular AlGaN QW and holes weakly localized on potential fluctuations.…”
Section: Model and Discussionmentioning
confidence: 99%